Analysis of deep-sea ferromanganese nodules using particle-induced X-ray emission technique - Stephen J Kirchner; H Oona; Steven J Perron; Quintus Fernando; John Jong-Hae Lee; Harry Zeitlin (PANGAEA, 2022)
Seven samples of ferromanganese nodules were analyzed using particle-induced X-ray emission technique (PIXE). All the samples were air-dried, crushed, and ground to a fine particle size (<100 mesh). Between 200 and 300 mg of each of the nodule samples was digested in a Teflon-lined stainless steel vessel with a 3:3:1 mixture of Ultrex HNO3, HF, and HC1 at 110 "C for several hours. A Nuclepore filter was impregnated with three 100-μL aliquots of the resulting solution and the thin target sandwiched between Kapton. The samples were irradiated with a 1-MeV proton beam for 1/2 h and the low-energy X-ray spectrum (0-10 keV) was collected. The high-energy (5-35 keV) emission spectrum obtained with a 2-MeV proton beam was collected for 1 h with a 0.004-in. A1 filter. The elemental concentrations present in the thin targets were calculated from the X-ray efficiency curves as described for the standard reference materials.